Mixed connective tissue disease in young Saudi patient with recurrent dental abscess: A case report - Faden, Asma’a; AlJamili, Alaa; Aljamili, Anfal; Alahmari, Sumayyah; Assiri, Abdulrahman (International Journal of Health Sciences, 2018)
Mixed connective tissue disease (MCTD) or overlap syndrome is a rare disease. It has overlapping features of more than one autoimmune disease with high titer of anti-ribonucleoprotein antibodies against U1. We present a 12-year-old Saudi male patient who was presented to the dental clinic complaining from non-healing oral ulcers and multiple periapical abscesses that not responsive to extractions and the use of oral antibiotics, these symptoms were accompanied with persistent fever, headache, muscle weakness, general malaise, and painful bilateral cervical lymphadenopathy. After a thorough investigation, he was diagnosed with (MCTD) and was managed dentally and medically accordingly.